Program compliance, weight loss and health profile changes in WHO obesity classes after very low energy dietary intervention - Wright, T.; Dawson, B.; Jalleh, Geoffrey; Guelfi, K. (Herbert Publications Limited, 2013)
Background: To assess program compliance, weight loss and health benefits in different WHO obesity classes (Class I: BMI 30-34.9; Class II: BMI 35.0-39.9; Class III: BMI 40+) after a very low energy diet intervention. Methods: Obese participants (n=1012) attending a private weight control clinic enrolled in a 26 week program. The first 12 weeks involved restricted energy intake (800 kcal/day), then gradual reintroduction of normal food (1200-1300 kcal/day), in conjunction with behaviour management. Body mass index (BMI), body mass, girths, blood pressure, cholesterol, triglycerides and glucose were measured before, during and after the 26 week intervention. Low compliance was defined as completing only 1-12 weeks, medium compliance 13-20 weeks and high compliance 21-26 weeks of the program. Results: Overall, 52% of participants achieved high compliance. Greater compliance resulted in greater weight loss and health profile changes across all obesity classes. With high compliance, for Class I, II and III groups respectively, 79, 77 and 79% lost 15% or more of initial body mass. Class III participants had greater reductions in body mass and most measured health markers than Class I and II persons. Conclusion: Higher program compliance is associated with greater weight reduction and health profile benefits in all WHO obesity classes, with larger changes occurring in the Class III group.